If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(x+11)=-40(8-x)
We move all terms to the left:
2(x+11)-(-40(8-x))=0
We add all the numbers together, and all the variables
2(x+11)-(-40(-1x+8))=0
We multiply parentheses
2x-(-40(-1x+8))+22=0
We calculate terms in parentheses: -(-40(-1x+8)), so:We get rid of parentheses
-40(-1x+8)
We multiply parentheses
40x-320
Back to the equation:
-(40x-320)
2x-40x+320+22=0
We add all the numbers together, and all the variables
-38x+342=0
We move all terms containing x to the left, all other terms to the right
-38x=-342
x=-342/-38
x=+9
| 5n/6=7/2 | | 2u+48=-4(u-6 | | 22=4f+2 | | (y-6)^4=0 | | -2p-5p=-9p-20 | | 5(x-2)(x-6)=0 | | -6(x+3)=-8x-30 | | 5x27=2x+9 | | 143=13b | | 0.5x-7=0.3x+5 | | -8-x=-4 | | a=(0.008)150 | | 35b=1680 | | z+-5=-7 | | 7×+2=10x+5 | | -7-4a=a-2 | | x/1=1/3 | | 9t^2=25 | | 15+12x=180 | | a=0.008•150 | | 40+55(m)=80+50(m) | | 4(y–3)=3(y+8) | | -1/2=4x^2+6x-18 | | 4(y–3)=3(y+8)–69 | | 3v=v+6v | | 9(x+7)=198 | | 3x-3x=-7 | | 7x+1=-3 | | 1/2x+10=1/2x+54 | | 7x+3(2−x)=4x+6 | | 9.00x=243 | | 3+9r+4=10r+15 |